KEEFEKTIFAN MODEL PROJECT BASED LEARNING (PJBL) BERBANTU MEDIA KONKRET TERHADAP MINAT DAN HASIL BELAJAR IPAS KELAS V SEKOLAH DASAR - NURHASANAH, ISFATHIA; WIJAYANTI, ARFILIA; SARY, RYKY MANDAR (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2024)
This research is based on the lack of innovation in learning models used by teachers in the learning process, especially in science and science subjects, so that students become passive and less interested in learning. In addition, the lack of use of learning media in the learning process will make students interest in learning decrease, resulting in low student learning outcomes. Therefore, innovation is needed in science and technology learning to foster the enthusiasm of students in the learning process, one of which is with the Project Based Learning (PjBL) model assisted by concrete media. The objectives to be achieved in this study are (1) to identify whether or not the Project Based Learning (PjBL) model assisted by concrete media is effective or not on the learning interest of class V students in learning science and science materials on changes in the earth's conditions due to natural factors; (2) identify the effectiveness or not of the Project Based Learning (PjBL) model assisted by concrete media on the learning outcomes of class V students in the learning of science and science materials on changes in the earth's conditions due to natural factors. This research was carried out at one of the State Elementary Schools in Sonokidul Village, Kunduran District, Blora Regency, in the odd semester of the 2024/2025 Academic Year. The population in this study is all class V students totaling 25, consisting of 14 male students and 11 female students. This study uses a quantitative approach with an experimental method. The experimental design used is a pre-experimental design in the form of one group pretest-posttest. The data collection techniques used in this study consist of interviews, observations, tests, and documentation. Based on data analysis, the results of the research were obtained, namely (1) the Project Based Learning (PjBL) model assisted by concrete media is effective on students learning interest in learning science science class V characterized by the acquisition of the percentage of students learning interest during three meetings ? 60%; (2) the Project Based Learning (PjBL) model assisted by concrete media is effective on the learning outcomes of students in class V science learning characterized by the acquisition of learning outcomes in the affective, cognitive, and psychomotor domains of students ? 70. ABSTRAKPenelitian ini dilatar belakangi oleh kurangnya inovasi model pembelajaran yang digunakan guru dalam proses pembelajaran khususnya pada mata pelajaran IPAS, sehingga peserta didik menjadi pasif dan kurang tertarik dalam pembelajaran. Selain itu, kurangnya penggunaan media pembelajaran dalam proses belajar akan membuat minat belajar peserta didik menurun yang mengakibatkan hasil belajar peserta didik rendah. Oleh karena itu, dibutuhkan inovasi dalam pembelajaran IPAS untuk menumbuhkan semangat dan antusias peserta didik dalam proses pembelajaran, salah satunya dengan model Project Based Learning (PjBL) berbantu media konkret. Tujuan yang hendak dicapai dalam penelitian ini, yaitu (1) mengidentifikasi efektif atau tidaknya model Project Based Learning (PjBL) berbantu media konkret terhadap minat belajar peserta didik kelas V pada pembelajaran IPAS materi perubahan kondisi bumi karena faktor alam; (2) mengidentifikasi efektif atau tidaknya model Project Based Learning (PjBL) berbantu media konkret terhadap hasil belajar peserta didik kelas V pada pembelajaran IPAS materi perubahan kondisi bumi karena faktor alam. Penelitian ini dilaksanakan di salah satu Sekolah Dasar Negeri di Desa Sonokidul, Kecamatan Kunduran, Kabupaten Blora, pada semester gasal Tahun Pelajaran 2024/2025. Populasi dalam penelitian ini adalah seluruh peserta didik kelas V yang berjumlah 25, terdiri dari 14 peserta didik laki-laki dan 11 peserta didik perempuan. Penelitian ini menggunakan pendekatan kuantitatif dengan metode eksperimen. Desain eksperimen yang digunakan yaitu pre-experimental design dengan bentuk one group pretest-posttest. Teknik pengumpulan data yang digunakan dalam penelitian ini terdiri dari wawancara, observasi, tes, dan dokumentasi. Berdasarkan analisis data, diperoleh hasil penelitian, yaitu (1) model Project Based Learning (PjBL) berbantu media konkret efektif terhadap minat belajar peserta didik pada pembelajaran IPAS kelas V ditandai dengan perolehan hasil persentase minat belajar peserta didik selama tiga pertemuan ? 60%; (2) model Project Based Learning (PjBL) berbantu media konkret efektif terhadap hasil belajar peserta didik pada pembelajaran IPAS kelas V ditandai dengan perolehan hasil belajar ranah afektif, kognitif, maupun psikomotorik peserta didik ? 70.